Bhava New Musical Composition | Karya Karawitan Baru Bhava - Dewangga, I Kadek Wahyu Bhaskara; Muryana, I Ketut (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
Bhava means spiritual vibration, which arises from the sincere devotion of the community to the gods; then, the gods will always give blessings and gifts. In addition to providing gifts, it is also believed that the gods will provide spirit energy (taksu) to the worshipper. Gamelan Gender Wayang generally accompanies Wayang Wong dances. But it differs from the Wayang Wong Dramatari in the Banjar Kawan Bangli Traditional Village, which uses three Gamelan barrages. From this uniqueness, the stylist wanted to raise the euphoria presented by the sound of the three instruments that the stylist poured into the Balaganjur Bebarongan musical work entitled Bhava. The feeling referred to by the stylist in this work is a sense of happiness, fear, and gratitude that arises and is owned by the people of Pura Dalem Purwa Banjar Kawan, Bangli, because of the sound of rumbling earthquakes, and the sound of lightning, but not accompanied by rain that occurred when Ida Bhatara Sakti Dalam Purwa Napak Pertiwi first after the repair of Barong (meodak). By looking at this phenomenon, the stylist was inspired to elevate the phenomenon into a work by combining barungan gamelan balaganjur bebarongan and kroncongan instruments. In theory, the creation of Bhava's musical work refers to the process of creating artwork according to I Wayan Dibia in the book Panca Sthiti Ngawi Sani in 2020, which consists of five stages, namely Ngawirasa (Inspiration), Ngawacak (Exploration), Ngarencana (Conception), Ngewangun (Execution), Ngebah (Production). Bhava is a religious theme presented by 17 performers using Balaganjur Bebarongan as the medium of expression with the addition of kroncongan instruments.